Melt property variation in GeSe2‐As2Se3‐PbSe glass ceramics for infrared gradient refractive index (GRIN) applications. (30th August 2018) - Yadav, Anupama; Buff, Andrew; Kang, Myungkoo; Sisken, Laura; Smith, Charmayne; Lonergan, Jason; Blanco, Cesar; Antia, Michael; Driggers, Megan; Kirk, Andrew; Rivero‐Baleine, Clara; Mayer, Theresa; et al.
Abstract: Melt size‐dependent physical property variation is examined in a multicomponent GeSe2 ‐As2 Se3 ‐PbSe chalcogenide glass developed for gradient refractive index applications. The impact of melting conditions on small (40 g) prototype laboratory‐scale melts extended to commercially‐relevant melt sizes (1.325 kg) have been studied and the role of thermal history variation on physical and optical property evolution in parent glass, the glass' crystallization behavior and postheat‐treated glass ceramics, is quantified. As‐melted glass morphology, optical homogeneity and heat treatment‐induced microstructure following a fixed, two‐step nucleation and growth protocol exhibit marked variation with melt size. These attributes are shown to impact crystallization behavior (growth rates, resulting crystalline phase formation) and induced effective refractive index change, neff, in the resulting optical nanocomposite. The magnitude of these changes is discussed based on thermal history related melt conditions.